Forest Semiosis - Jacob Vangeest (Footprint)
This article operationalizes Bernard Stiegler’s conceptualization of the Neganthropocene, expanding his consideration of thinking (penser) as care (panser) or pænsée beyond the anthropo-techne limitations of his thought through the notion of a posthuman asignifying semiotics. It begins with an overview of Stiegler’s notion of the Neganthropocene as a mode of epochal thought building towards noesis and pænsée with the use of epiphylogenetic and exosomatic memory systems. Here, Stiegler’s approach is exposed as anthropo-techne centric, which in turn limits the possibilities of noesis. Turning to the work of C.S. Peirce, Gilles Deleuze, and Felix Guattari, an alternative formulation of epiphylogenetic memory is provided through the interrelation of trees and forests: in particular the coastal redwood (sequoia sempervirens). This asignifying semiotics provides the criteria for infusing Stiegler’s epiphylogenesis beyond the human. In turn, Stiegler is brought closer to the theories of entangled care presented in the work of theorists such as María Puig De La Bellacasa and Natasha Myers, allowing for a more dynamic design process.